Effects of rest interval and training intensity on jumping performance: a systematic review and meta-analysis investigating post-activation performance enhancement - Chen, Yiyan; Su, Qing; Yang, Juan; Li, Gen; Zhang, Shiyan; Lv, Yuanyuan; Yu, Laikang (Frontiers in Physiology, 2023)
Background: There is no clear agreement regarding the ideal rest interval and training intensity to optimize post-activation performance enhancement (PAPE) after barbell squat (BS). Therefore, the aim of this study was to investigate the effects of rest interval and training intensity on jumping performance due to PAPE. Methods: Searches were performed in PubMed, Web of Science, and EBSCO databases. We included studies that satisfied the following criteria: (1) eligible studies should be randomized controlled trials; (2) eligible studies should investigate the acute effect of barbell squat-induced PAPE on jump performance; (3) eligible studies should use countermovement jump, squat jump, or vertical jump as the outcome measure. Results: From 2518 search records initially identified, 19 studies were eligible for meta-analysis. Our meta-analysis results showed that BS had no significant effect on improving jumping performance due to PAPE (Cohen’s d = 0.09, p = 0.08). Subgroup analysis showed that rest interval between 0-1 min was detrimental to jumping performance (Cohen’s d = -0.33, p < 0.01), while rest intervals between 4-7 min (Cohen’s d = 0.31, p < 0.01) and 8-9 min (Cohen’s d = 0.26, p = 0.02) provided favorable jumping performance outcomes. In addition, low-intensity and moderate-intensity BS had no significant effect on jump performance, while high-intensity BS showed results consistent with rest interval. Conclusions: Our study indicated that both low-intensity and moderate-intensity BS failed to induce PAPE, and it is recommended that future studies use high-intensity BS to induce PAPE. A rest interval of 4-9 min had a beneficial impact on jump height, and an interval range of 4-7 min seems to be the best rest interval between conditioning activity and jumping performance.